For the sake of simplicity: Applying software design parsimony to the content of information system ontologies - Tambassi, Timothy (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2023)
Although many information system ontologies (ISOs) claim to be parsimonious, the notion of parsimony seems to influence the debate on ISOs only at the level of vague and uncritical assumption. To challenge this trend, the paper aims to clarify what it means for ISOs to be parsimonious. Specifically, section 2 shows that parsimony in computer science generally concerns software design and, together with elegance, is one of the two aspects of the broader notion of simplicity. Section 3 transforms the main claims of parsimony in software design into claims about the content of ISOs, the combination of which is hereafter called “parsimony of content”—where “content” refers only to the content of ISOs. Sections 4-7 discuss the application of this parsimony to the design of ISOs, and outline different kinds (and combinations) of parsimony of content. Finally, section 8 considers whether parsimony of content could provide some criteria both for selecting and/or classifying the contents of ISOs and for choosing between different and equally consistent ISOs.